ISOLATION STUDIES FROM STEM EXTRACT OF PISTACIA INTEGERRIMA STEW. EX BRAND - Yamin Bibi; Abdul Qayyum; Sobia Nisa; Abdul Waheed; Muhammad Fayyaz Chaudhary (Journal of the Chilean Chemical Society, 2016)
Plants have been source of fantastic natural compounds that range in complexity. Chemical studies on traditional medicinal plants have led to discovery of potent bioactive components. Pistacia integerrima belonging to family Anacardiaceae has been traditionally effective for rheumatic pain, analgesic and antipyretic effects and used in treatment of coughs, phthisis, asthma and dysentery. Natural products have served as basis for compounds to be utilized in drug discovery. Stem extract of Pistacia integerrima was investigated with the aim to find some novel components that can later be used as drugs or active pharmaceutical intermediates. Plant material was collected from Margalla Hills Islamabad, shade dried and subjected to cold maceration technique for extraction. Crude extract was partitioned into different fractions on polarity basis. Repeated normal and reverse phase column chromatography of ethyl acetate fraction supported by Thin Layer Chromatography have led to the isolation of pure single compound. Isolated compound was further analyzed towards structural elucidation using LC-MS, IR and NMR spectroscopy. Present finding will be a useful and novel addition in already known chemical components from Pistacia integerrima.